2017
DOI: 10.1128/aem.03103-16
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Fungal Phenolic UDP Glycosyltransferases from Absidia coerulea and Rhizopus japonicus

Abstract: In the present study, two novel phenolic UDP glycosyltransferases (PUGTs), UGT58A1 and UGT59A1, which can transfer sugar moieties from active donors to phenolic acceptors to generate corresponding glycosides, were identified in the fungal kingdom. UGT58A1 (from Absidia coerulea) and UGT59A1 (from Rhizopus japonicas) share a low degree of homology with known UGTs from animals, plants, bacteria, and viruses. These two P-UGTs are membrane-bound proteins with an N-terminal signal peptide and a transmembrane domain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 39 publications
(55 reference statements)
1
21
0
Order By: Relevance
“…The easily scalable total biosynthesis of such molecules is achieved by: (i) expressing appropriate PKS subunit pairs to afford natural or unnatural BDL congeners in a yeast chassis; and (ii) coexpressing a novel fungal type II/III detoxification module to decorate the polyketide scaffolds with a 4-O-methylglucose biosynthon. Although enzymes for the biosynthetic glycosylation of various bioactive aglycones have been characterized from bacterial or plant sources (1, 7), the first fungal enzymes with significant aglycone promiscuity were only identified in 2017 (6,9). Considering the biosynthetic and biodegraditive capacities of filamentous fungi, and their proven proficiency in glycosylating various scaffolds (11-16, 20, 41), extending the pool of biocatalysts with novel fungal enzymes, such as the B. bassiana GT-MT methylglucosylation module for the glycodiversification (3,57) of various aglycones, is highly promising.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The easily scalable total biosynthesis of such molecules is achieved by: (i) expressing appropriate PKS subunit pairs to afford natural or unnatural BDL congeners in a yeast chassis; and (ii) coexpressing a novel fungal type II/III detoxification module to decorate the polyketide scaffolds with a 4-O-methylglucose biosynthon. Although enzymes for the biosynthetic glycosylation of various bioactive aglycones have been characterized from bacterial or plant sources (1, 7), the first fungal enzymes with significant aglycone promiscuity were only identified in 2017 (6,9). Considering the biosynthetic and biodegraditive capacities of filamentous fungi, and their proven proficiency in glycosylating various scaffolds (11-16, 20, 41), extending the pool of biocatalysts with novel fungal enzymes, such as the B. bassiana GT-MT methylglucosylation module for the glycodiversification (3,57) of various aglycones, is highly promising.…”
Section: Discussionmentioning
confidence: 99%
“…narrow-spectrum sterol 3β-glucosyltransferases were identified from various yeast strains until recently. While this work was in progress, the discovery of two disparate, nonorthologous phenolic GT groups from three basidiomycete fungi were reported (MhGT1 from Mucor hiemalis, and UGT58A1/UGT59A1 from Rhizopus japonicus and Absidia coerulea, respectively) (6,9). These discoveries indicated that despite their very low similarity to known enzymes from other organisms (6,9,10), promiscuous yet regio-and stereospecific GTs from the kingdom Fungi can indeed be identified and harnessed for synthetic biology (6,9).…”
Section: Significancementioning
confidence: 98%
See 1 more Smart Citation
“…The purified UGT88E18 was applied to the in vitro reaction with calycosin (Compound 1) or formononetin (Compound 2, another important isoflavonoid present in R. astragali) as the Chemical glucosylation is notoriously complicated because of various disadvantages such as low efficiency, poor stereospecificity, a series of protection and deprotection steps, and environmental pollution [14]. In this respect, enzymatic glucosylation using regio-and stereoselective UGTs can alleviate these disadvantages [15,16]. Extensive studies indicate that sucrose synthase (SuSy) is a versatile biocatalyst that can synthesize costly uridine diphosphate glucose (UDPG) from abundant and cheap sucrose and catalytic amounts of uridine diphosphate (UDP) [17,18].…”
Section: Regioselective Glucosylation Of Calycosin and Formononetin Bmentioning
confidence: 99%
“…The poor aqueous solubility of natural products resulted in a low absorption and a short retention time in the intestine [21]. Glycosylation mediated by UGTs transfers the hydrophilic sugar moieties to natural products, which can significantly enhance their solubility and thus improve their bioavailability and pharmacodynamics [29,30]. The aqueous solubility of ginsenoside Rg3 was limited to 90 µM.…”
Section: Aqueous Solubility Of Ginsenoside Rd12mentioning
confidence: 99%